Using Quizziz Application as an Evaluation Media for Online Learning in Citizenship Education Courses - Novita Sari; Mukhamad Murdiono; Edwin Nurdiansyah; Alfiandra Alfiandra; Rike Erlande (STAI Hubbulwathan Duri, 2023)
This study aims to describe the use of the Quizizz Application as an evaluation medium for online learning in Citizenship Education courses. This study uses qualitative research with descriptive analysis methods, and data collection techniques used include interviews, observations, and surveys. The subjects of this research are class A and class B students of the law faculty class of 2021. To collect data, researchers used questionnaires and observation sheets. They use descriptive analysis to analyze it. The results of the study show that the Quizizz application as an evaluation medium is effectively used for online learning in citizenship education courses, which can be seen from the assessments carried out through live quizzes. And also, evaluation of learning using Quizizz is considered to be able to facilitate educators in conducting detailed and objective assessments so that it is more practical and fast.